2022
DOI: 10.5435/jaaos-d-22-00302
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Dysplastic Hips Undergoing Hip Arthroscopy Achieve Equivalent Patient Reported Outcomes When Compared With Hips With Normal Acetabular Coverage: A Systematic Review and Meta-Analysis

Abstract: Purpose:To systematically review and meta-analyze studies reporting lateral center edge angle as it relates to patient-reported outcome (PRO) measures and clinically notable outcome assessments for patients undergoing hip arthroscopy for femoroacetabular impingement syndrome or labral pathology with borderline dysplastic hips (BDH).Methods:PubMed, EMBASE, and the Web of Science Core Collection databases were queried for articles evaluating lateral center edge angle as a predictor of PRO after hip arthroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…This durability of outcome improvement suggests that the improvement seen in previous short-term and midterm follow-up studies is sustained at long-term follow-up. 3,15,16 A recent meta-analysis by Krivicich et al, 14 evaluating 989 hips at 3-year follow-up, found minimal differences in PROs between patients with BHD and those without. One may reasonably point out that in the current study, many of the postoperative PRO scores for the BHD group were lower than those of controls without reaching statistical significance; however, it is important to note that the delta values from preoperative to postoperative scores were not statistically different aside from VAS pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This durability of outcome improvement suggests that the improvement seen in previous short-term and midterm follow-up studies is sustained at long-term follow-up. 3,15,16 A recent meta-analysis by Krivicich et al, 14 evaluating 989 hips at 3-year follow-up, found minimal differences in PROs between patients with BHD and those without. One may reasonably point out that in the current study, many of the postoperative PRO scores for the BHD group were lower than those of controls without reaching statistical significance; however, it is important to note that the delta values from preoperative to postoperative scores were not statistically different aside from VAS pain.…”
Section: Discussionmentioning
confidence: 99%
“…At short-term follow-up, patients with BHD have demonstrated significant improvements in postoperative patientreported outcomes (PROs) and a high rate of achievement of clinically significant outcomes, without significant differences compared with patients without BHD. 14,15,21 At midterm follow-up, these outcomes are sustained with favorable PROs and high rates of clinically significant outcome achievement. 3,16 However, a paucity of literature is available regarding long-term outcomes for patients with FAIS in the setting of BHD, and the study that does exist is limited by the lack of comparative control groups.…”
Section: Patients With Femoroacetabular Impingement Syndrome (Fais) A...mentioning
confidence: 99%
“…Валидность -показатель того, насколько хорошо предлагаемый тест и его результат соответствуют поставленным задачам исследования. Доказано, что оригинальный опросник Hip Preservation Surgery Expectations Survey является валидным [20]. Прямой и обратный перевод, экспертная оценка различий и редактирование с учетом комментариев пациентов в рамках пилотного исследования позволили сохранить валидность оригинальной анкеты, что доказывают значения коэффициента внутриклассовой корреляции (0,82) и коэффициент α Кронбаха (0,945).…”
Section: Discussionunclassified
“…Многие авторы считают оправданной артроскопическую коррекцию ФАИ [13,14,15,16], так как при успешном исходе использование данной методики позволяет уменьшить симптомы, мешающие вести активный образ жизни, и отсрочить более травматичные и обширные вмешательства у молодых пациентов [1,2,3]. Однако удовлетворенность пациента результатом данного метода лечения колеблется от 68 до 100% [17,18,19,20]. Удовлетворенность пациента зависит от ряда факторов, таких как достигнутое функциональное состояние тазобедренного сустава после операции, наличие боли и способность выполнять повседневные задачи, которые вызывали трудности до операции [4,5,6,21].…”
Section: Introductionunclassified